Design of a dual‐beam cavity‐backed patch antenna for future fifth generation wireless networks. Issue 10 (3rd May 2018) - Tan, Jingyu; Jiang, Wen; Gong, Shuxi; Cheng, Tong; Ren, Junyi; Zhang, Kunzhe
Abstract : A dual‐beam cavity‐backed patch antenna is presented for the future millimetre‐wave (mm‐Wave) fifth generation wireless networks. The proposed antenna comprises a substrate integrated waveguide cavity and a symmetrical patch. The antenna exhibits a bandwidth range from 27.8 to 30.9 GHz with the fractional bandwidth of 10.6%. The radiation patterns are dual beam and peak gains are above 8.4 dB across the passband. Two beam directions are at  + 47° and −47° with respect to the broadside direction. It shows a good agreement between the simulated and measured results.